A personal leadership statement (2025)
Teaching English as a foreign language is not only about transmitting knowledge but also about leading and empowering your learners for them to be authentic. The role of leadership in the classroom is essential in terms of knowing and recognizing students’ needs to reach the main goal. The purpose of this paper is to explore how authentic leadership might be a compass for foreign language teachers, emphasizing their teacher practice. The following statement aims to guide teachers to enact authentic leadership to influence students morally. Therefore, this paper suggests how teachers can implement authentic leadership through assumptions, implications, and empowerment to enhance their teaching practice. An environment where morality, integrity, and authenticity are the main objective of this personal leadership statement.